Economics and laboratory efficiency of atrial fibrillation ablation. (January 2022) - Kowalski, Marcin; Shah, Rina; Akhrass, Philippe; Parikh, Valay
Abstract : Purpose of review: Atrial fibrillation is a growing public health problem and is associated with an increased risk of comorbidities with enormous socioeconomic implications. This review article focuses on fiscal burden of atrial fibrillation on the healthcare system and economic value of atrial fibrillation ablations brought to the patient and the payers by improvement in outcomes and reduction in treatment costs. Recent findings: This article summarizes the recently published studies evaluating the economic impact of atrial fibrillation treatment. Catheter ablation have shown to be the most successful strategy for treatment of defibrillation. However, repeat ablation is associated with higher costs, over and above any subsequent procedural costs, compared with a single ablation procedure for atrial fibrillation. Cryoballoon ablation has been shown to have fewer repeat ablations than radiofrequency ablations, which resulted in overall cost reduction. Improvement in laboratory efficiency, better utilization of laboratory resources and same-day discharge strategy can lead to further healthcare savings and increase in value to all stakeholders. Summary: The value of healthcare delivery for patient with atrial fibrillation can be improved by advancement in technology that demonstrates cost reduction to the health system and outcomes improvements. Implementation of tactics that decrease cost and improve outcomes can alleviate some of the financial strain on healthcare systems, which is of extreme importance in the current climate.